Improved Safety of Hybrid Electroconvulsive Therapy Compared With Standard Electroconvulsive Therapy in Patients With Major Depressive Disorder: A Randomized, Double-Blind, Parallel-Group Pilot Trial - Zhang, Jing-ya; Xu, Shu-xian; Zeng, Lun; Chen, Li-chang; Li, Jia; Jiang, Zhao-yun; Tan, Bai-jian; Gu, Chen-long; Lai, Wen-tao; Kong, Xiao-ming; Wang, Jian; Rong, Han; et al. (Frontiers in Psychiatry, 2022)
Objectives: ECT is a rapid and effective treatment for depression. While efficacy is often remarkable over the initial 3–4 sessions, the efficacy of later sessions is less rapid, and the side-effects, especially cognitive impairment limit its use. To preliminarily compare the efficacy and acceptability of a novel hybrid-ECT (HECT) protocol for patients with major depressive disorder (MDD) with standard ECT, we conducted this pilot trial. Methods: Thirty patients were randomly assigned to ECT or HECT. Both arms received three ECT sessions (phase 1) but, in phase 2, the HECT arm received low-charge electrotherapy instead of ECT. The primary outcome was the change in 24-item Hamilton depression rating scale (HAMD-24) scores between baseline and the end of treatment. Cognitive function was assessed by repeatable battery for the assessment of neuropsychological status (RBANS), Stroop color word, and orientation recovery tests (ORT). Safety was measured by the drop-out rate and adverse events (AEs). Four visits were conducted at baseline, post-phase 1, post-phase 2, and at one-month follow-up. Trial registration: Chinese Clinical Trial Registry (http://www.chictr.org.cn/), identifier: ChiCTR1900027701. Results: Patients in both arms showed significant within-group improvements in HAMD-24, but the between-group differences were nonsignificant. Participants in the HECT arm outperformed ECT patients for most cognitive tests at the end of treatment or at follow-up. There was a significantly lower AE rate and shorter ORT in phase 2 of the HECT arm. Conclusions: In this pilot trial, HECT was associated with fewer AEs and better cognitive function including executive and memory function, but its possible similar antidepressive efficacy needs to be further investigated in future.